Skilled Birth Attendance among Women in Tharaka-Nithi County, Kenya - Eliphas Gitonga (Advances in Public Health)
Background. The burden of maternal mortality is concentrated in sub-Saharan Africa with an estimation of 500 000 deaths annually. In 2012, about forty million births occurred without a skilled attendant in developing countries. Skilled birth attendance improves maternal and newborn survival. The aim of this study therefore was to establish the level of skilled birth attendance and the associated factors. Methods. A cross-sectional survey was carried out using structured questionnaires as tools of data collection. Systematic sampling was used to select the respondents from the facilities that were stratified. The dependent variable was skilled birth attendance. Descriptive statistics were used to generate proportions and percentages while chi-square and Fisher’s exact tests were used to draw inferences. Association was significant if P<0.05. Results. The level of utilisation of skilled birth attendance was 77%. Skilled birth attendance was noted to be associated with age, level of education, average family income, parity, distance to the health facility, timing of initiation of antenatal care, level of facility attended during pregnancy, and birth preparedness status. Conclusion. The level of skilled birth attendance among women in Tharaka-Nithi County, Kenya, despite being higher than in some counties, requires improvement.